Rose cultivars for biomonitoring of air quality - Wanjala Sylvia Nafula; László Orlóci; Szilvia Kisvarga; Gábor Boronkay; Béla Tóthmérész; Stewart Ajele; Vanda Éva Abriha-Molnár; Edina Simon (Heliyon, 2025)
The usefulness of rose cultivars for air quality monitoring was assessed; the assessment is based on the Air Pollution Tolerance Index and the Air Quality Index. A total of 11 cultivars of roses were evaluated; they were collected from a peri-urban area of the city of Budapest (Hungary). The Air Pollution Tolerance Index is based on the physiological and biochemical parameters of the specimens, including the relative water content, leaf pH, ascorbic acid, and total chlorophyll. The Air Quality Index is based on the concentration of particulate matter, NOx, and SO2. We found that the Air Pollution Tolerance Index values of the selected rose cultivars ranged between 6.8 and 10.5, suggesting that these rose cultivars are sensitive indicators of air pollution. Significant differences were found among the cultivars based on the concentration of ascorbic acid, total chlorophyll, and relative water content. Seasonal differences were found in the Air Quality Index; a significantly higher value was found in autumn, and significant differences were also found among seasons based on the air pollutants. Our findings suggest that the studied rose cultivars are useful indicators of air pollution. Planting rose cultivars in urban green spaces alongside established species that are tolerant to polluted air provides a good opportunity for bioindication. Besides their aesthetic value, these plants may prove to be useful in urban greening projects.